(untitled) (Texas Journal of Medical Science, 2023)
The article provides data on the study of the subject of simulation training in surgery, gynecology, dentistry, and also focuses on the repeatability of medical skills in SB on various mannequins, simulators, which makes it possible to carry out various practical skills in surgery, therapy, obstetrics-gynecology, and also paw roscopic placement in various organs of the abdominal cavity to the point of automatism. Such mastery of the technique and practical skills allows you to accurately perform all medical procedures during surgery and examinations